Reducing chemical fertilizer use mitigates obstacles in intensive monocropping of cucumber: a probable role of Pseudomonads in the process. (19th May 2017) - Zhang, Yang; Li, Qing; Shen, Min; Kang, Yijun; Hu, Jian
ABSTRACT: A five-year continuous monocropping of cucumber in a greenhouse receiving 50% NPK and 100% NPK was conducted to explore if reducing chemical fertilizer use can mitigate obstacles in intensive monocropping, and the microbial mechanism of the process. Significant decreases in living seedling rates and total yields with time were exhibited in the 100% NPK treatments, showing an obvious obstacles event, which can be mitigated by reducing fertilizer use. It was found that both total yields and living seedling rates were negatively correlated with the proportion of Fusarium oxysporum f. sp. cucumerinum (a known cucumber wilt pathogen) in F. oxysporum, suggesting the two fungal groups out of balance in the rhizosphere, was the key factor for the decline in cucumber growth in the monocropping system. Furthermore, the abundance of pseudomonas group, not hydrogen cyanide- or phenazine-producing pseudomonas, can act as the defender against possible fungal pathogens. The opposite relationships between HCN-producing pseudomonas and two plant indicators (cucumber yield and living seedling rate) suggested that HCN-producing pseudomonas exerted positive effects only when cucumber plants' density was above a certain threshold. The Redundancy Analysis (RDA) showed that changes in soil microbial population size, especially in pseudomonas groups, contributed to the mitigation process.